A Novel Security threat in Optical Flow Switched Architectures - R.Vinoth Kumar, A.Rajalakshmi, S.Ganesh Kumar (International Journal of Advanced Science and Technology, 2019)
Optical Flow Switching is a scalable, cost-effective architecture for long-haul Internet backbones. The architecture addresses the power issue of store-and-forward packet switching in future MAN-WAN Terabit networks. In this paper, we discuss about novel security vulnerability, BoOST (Border Optical Security Threat) in optical flow switched architecture. The impact of BoOST on throughput and latency are presented with simulation experiments. Further, prevention and countermeasure for the proposal is highlighted.